Guimarães Rosa and the literary exhibition of the vernacular. Issue 5 (3rd May 2020) - Welge, Jobst
ABSTRACT: This article addresses the paradoxical relation of the literary work of the Brazilian author João Guimarães Rosa to the field of world literature. On the one hand, this work is distinguished by an insistent worlding function, insofar as it is a prime example of a regionalist modernism that transcends its local and regionally specific context into universal, global, and metaphysical dimensions of meaning. On the other hand, the author has created a virtually unique linguistic idiom that requires heightened concentration on the part of the reader and poses enormous challenges for translation. The article argues that this paradox may be usefully discussed by way of the category of the vernacular, as it derives from Dante's treatise De vulgari eloquentia . The vernacular reshaping of the language emphasises the mutability of the world and the striving of the literary discourse to reconnect itself to some sense of poetic immediacy. Matters of linguistic resistance and self-conscious, meta-linguistic or meta-translational passages will be analysed insofar as they serve the literary exhibition of the vernacular as something that courts yet is already removed from oral/popular immediacy. Comments on a long novella ( O recado do morro ) and an epic novel ( Grande Sertão: Veredas ), both from 1956, explore the relation between the word, the vernacular, and the world.